Challenges in Managing Sars-Cov-2 Positive Child with Juvenile Onset Recurrent Respiratory Papillomatosis: A Case Report with Review of Literature - Dutta, Heempali Das; Pradhan, Bibhu (Tribhuvan University Journal, 2020)
Juvenile-Onset Recurrent Respiratory Papillomatosis (JORRP) is a viral infection caused by Human papilloma virus 6, 11 which presents as hoarseness, shortness of breath and in severe form may present with acute airway obstruction because of papillomatous growth obstructing the larynx. Urgent surgical intervention may be needed to secure the airway. In the present situation of Coronavirus disease-2019 (COVID-19) pandemic, the case of JORRP with COVID-19 positive state is a challenging situation because any laryngeal or airway surgery is associated with high amount of aerosol generation. Air borne transmission is one of the major routes of transmission for SARS-Cov-2 virus which may result in spread of COVID-19 among to the health care provider.In this situation, it is better to avoid delay laryngeal surgery if the patient is not in acute airway obstruction requiring urgent surgical intervention. Otherwise, if the urgent surgery has to be done, then it should be done properly by following institutional guidelines to avoid the spread of the disease and to be done with all precautionary biosafety measures like use of personal protective equipment (PPE), N95 mask and proper donning and doffing.